A supporting-electrolyte-free four-compartment electrochemical reactor for aqueous and organic phase electrosynthesis - Huan Wu; Baoquan Liu; Chenliang Su; Deyin Chen; Longhao Jiao; Huajun Zheng; Lianbang Wang; Zhenyuan Teng; Lianchong Shao; Yinghua Xu; Bin Liu (Proceedings of the National Academy of Sciences, 2025)
Electrosynthesis offers a promising method to make valuable chemicals under mild conditions; however, its application has been greatly hampered by issues including the requirement of a supporting electrolyte, the limited solubility of reactant(s) in electrochemical compartments, the complex product(s) separation processes, etc. Herein, we innovatively present a four-compartment electrochemical reactor equipped with delicately designed active species diffusion membrane electrodes. Four compartments include two chemical (reduction and oxidation) compartments and two electrochemical (cathode and anode) compartments. The unique membrane electrodes physically separate the chemical compartments (containing organic reactants in pure solvent) from the electrochemical compartments (containing supporting electrolytes), while allowing electrosynthesis of high-value-added chemicals in both nonconducting aqueous and organic environments without the need of a supporting electrolyte. The reactor is able to drive both the anodic electrosynthesis (e.g., oxidation with a halogenation yield > 93%) and the cathodic electrosynthesis (e.g., reduction with a hydrogenation yield > 95% and a deuteration incorporation > 85%). The batch four-compartment electrochemical reactor can be engineered into a continuous type, where substrates in pure solvent can be converted into products with a conversion > 90% as they travel from the inlet to the outlet of the continuous reactor.